Islamic teachings on poverty in the light of modern theories and realities (2013)
This paper examines the position of Islam on the phenomenon of poverty by interacting its concept, nature and theories with the conventional notion of it. The study discovered that Islam, similar to the secular conception of poverty, has given adequate attention to poverty from socio-economic and cultural angles. Poverty is not an Islamic heritage as viewed by some, instead, it is a religion and a way of life that advocates the complete meeting of the legitimate material needs of man. There is also the school of thought, which holds that efforts’ at acquiring wealth need not be made as Allah, through pre-destination, determines the financial status of individuals. The position of Islam is that this cannot be ascertained until after death. Therefore, man has to continue to legitimately and legally strive to acquire wealth. In cases when poverty is inevitable, Islam mitigates its negative impacts to the barest minimum. Hence, affluence rather than poverty is the Objective of Islam.